2016
DOI: 10.1021/acs.biomac.6b00223
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Structural Insights into Enzymatic Depolymerization of Polylactic Acid and Other Polyesters by Microbial Carboxylesterases

Abstract: Polylactic acid (PLA) is a biodegradable polyester derived from renewable resources, which is a leading candidate for the replacement of traditional petroleum-based polymers. Since the global production of PLA is quickly growing, there is an urgent need for the development of efficient recycling technologies, which will produce lactic acid instead of CO2 as the final product. After screening 90 purified microbial α/β-hydrolases, we identified hydrolytic activity against emulsified PLA in two uncharacterized pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
130
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(133 citation statements)
references
References 70 publications
2
130
1
Order By: Relevance
“…PHB, PBS and PCL) (Sekiguchi et al, 2011), although the mechanisms involved were not previously identified. In another study that performed an in vitro screening for PLA esterases, researchers identified that the enzyme ABO2449 encoded by Alcanivorax borkumensis had a strong hydrolytic activity on PLA as well as on a range of other aliphatic polyesters, that is, PHBV, PCL and PES (Hajighasemi et al, 2016). A homologue of the ABO2449 α/β-hydrolase was encoded by Alcanivorax sp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PHB, PBS and PCL) (Sekiguchi et al, 2011), although the mechanisms involved were not previously identified. In another study that performed an in vitro screening for PLA esterases, researchers identified that the enzyme ABO2449 encoded by Alcanivorax borkumensis had a strong hydrolytic activity on PLA as well as on a range of other aliphatic polyesters, that is, PHBV, PCL and PES (Hajighasemi et al, 2016). A homologue of the ABO2449 α/β-hydrolase was encoded by Alcanivorax sp.…”
Section: Discussionmentioning
confidence: 99%
“…A previously characterized esterase from Alcanivorax borkumensis that showed a strong hydrolytic activity on aliphatic polyesters (ABO2449; Hajighasemi et al, 2016) and that had a conserved homologue in our Alcanivorax sp. 24, i.e.…”
Section: Proteomic Analysis To Identify the Secreted Esterase(s) Respmentioning
confidence: 99%
See 1 more Smart Citation
“…Supercritical depolymerization in water and alcohols has been demonstrated with epoxy and polyethylene. Enzymatic depolymerization of polylactic acid and other polyesters is known . Devulcanization is possible, and was used in both world wars to supplement virgin rubber supplies, but modern vulcanization chemistry has made this increasingly difficult …”
Section: Enabling Technologiesmentioning
confidence: 99%
“…Hajighasemi et al . described a putative PLA‐degrading mechanism of a bacterial carboxylesterase, based on structural studies complex with polyethylene glycol (PEG) molecule, which is completely different from cutinase. But the mode of hydrolyzing action of cutinases with PLAs is not fully understood.…”
Section: Introductionmentioning
confidence: 99%